The Potential of Potassium Fertilizers in Improving the Availability and Uptake of Potassium in Rice Grown on Entisol - Sri Hartati; . Suryono; Lia Sari Purnama (UNIVERSITY OF LAMPUNG, 2019)
Entisol is a marginal soil spreading over some areas in Indonesia. It has loose soil consistency, low aggregation rates, sensitive to erosion, and low nutrient content. Entisol has high K deficiency. Potassium plays an important role in rice growth (Oryza sativa). The aim of the research was to study the effects of type and dose of potassium fertilizers on available K in Entisol and its uptake by rice plants. The study was arranged in a Randomized Complete Block Design with 2 factors, i.e. the types of potassium fertilizers (KCl, ZK and KNO3) and doses of potassium fertilizers (0 kg K2O ha-1, 50 kg K2O ha-1, 100 kg K2O ha-1, and 150 kg K2O ha-1), with three replications. The results showed that the type of potassium fertilizers applied resulted in similar effects on almost all soil and plant parameters. The dose of potassium fertilizers significantly affected all soil and plant parameters, the higher the doses, the higher the values of the parameters observed.